2006
DOI: 10.3892/ijo.29.1.175
|View full text |Cite
|
Sign up to set email alerts
|

HAS3-related hyaluronan enhances biological activities necessary for metastasis of osteosarcoma cells

Abstract: Abstract. Several studies have suggested that increased production of hyaluronan (HA) is associated with metastatic behavior in various malignant tumors. To our knowledge, HA molecular weights required for metastasis are still unsolved in osteosarcoma. We examined the size of HA and hyaluronan synthase (HAS) isoforms related to biological functions required for metastasis in the LM8 stably highly metastatic osteosarcoma cell line. We found that HA of molecular weight which HAS3 produces enhanced biological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Data from the overexpression of HAS1-3 or perturbation of hyaluronan production in several cancer cell lines have suggested that the accumulation of hyaluronan stimulates growth, survival, invasion, and metastasis of cancer cells (66 -68). Thus, it is likely that both hyaluronan and versican participate in the formation of a permissive microenvironment around the LMS tumor cells to promote their proliferation (42,69). It is interesting to note that our data show that a maximal proliferative response is achieved when the two molecules are added together, suggesting that a versican-hyaluronan complex may be optimal for the proliferative response of the LMS cells.…”
Section: Discussionmentioning
confidence: 57%
“…Data from the overexpression of HAS1-3 or perturbation of hyaluronan production in several cancer cell lines have suggested that the accumulation of hyaluronan stimulates growth, survival, invasion, and metastasis of cancer cells (66 -68). Thus, it is likely that both hyaluronan and versican participate in the formation of a permissive microenvironment around the LMS tumor cells to promote their proliferation (42,69). It is interesting to note that our data show that a maximal proliferative response is achieved when the two molecules are added together, suggesting that a versican-hyaluronan complex may be optimal for the proliferative response of the LMS cells.…”
Section: Discussionmentioning
confidence: 57%
“…Using H-ras-transformed C3 fibroblasts, Hall et al (1994) demonstrated that HA leads to FAK tyrosine phosphorylation and augmented the formation of focal adhesions (36). Furthermore, in osteosarcoma cells, HA stimulates the phosphorylation of FAK and ERK1/2 (20). Despite the previously observed link between CD44 and FAK activation (37)(38), CD44 blocking antibodies had no influence on FAK degradation in ESCC.…”
Section: Discussionmentioning
confidence: 75%
“…showed that metastasis‐associated properties of cancer cells such as invasion and proliferation are enhanced by lower molecular weight forms of HA that are characteristic of HAS3 activity (Itano and Kimata, 2002). In contrast, HAS2 is believed to deliver higher molecular weight HA that supports pericellular coat formation and thus inhibits a malignant tumour cell phenotype (Tofuku et al. , 2006) unless it is further processed by for example hyaluronidases (Stern, 2008).…”
Section: Discussionmentioning
confidence: 99%